Formation of single domain state and spontaneous backswitching in SBN single crystal. Issue 1 (27th May 2016) - Kolchina, E. A.; Neradovskiy, M. M.; Shikhova, V. A.; Pelegov, D.V.; Shur, V. Ya.; Ivleva, L. I.; Dec, J.
ABSTRACT: Formation of the single domain state and spontaneous backswitching have been studied in polar cut single crystals of relaxor ferroelectric strontium-barium niobate Srx Ba1-x Nb2 O6 with x = 0.61. The piezoresponse force microscopy has been used for domain visualization. Two methods of creation of the single domain state were applied: (1) cyclic switching below freezing temperature and (2) cooling from the temperature corresponding to relaxor phase to room temperature in constant field. The domain structure, appearing as a result of spontaneous backswitching after fast removal of the external field, have been revealed and analyzed.